The soluble sugars determination in cucurbitaceae species under water stress and recovery periods - (:unkn) unknown (My University, 2009)
The soluble sugars detected in leaves of the two cucumber cultivars from Turkey, Beit Alpha 434 (B. 434) and Cengelkoy (C.M.C) and Cucumis melo var. flexuosus (L.) Naudin (Acur - snake cucumber), Cucurbita pepo L. (summer squash) and Ecballium elaterium (L.) A. Rich. (squirting cucumber) grown in conditions of normal water supply and under moderate (MS) and severe (SS) water stress levels, in addition, the effect of recovery phases investigated 4days (4d) fully rewatering. GLC (gas liquid chromatography) analysis of sugars showed that Cucumis sativus and related species contained other sugar compounds such as mannitol (man.), inositol (inos.) and raffinose (raf.) in addition to glucose (glu.), fructose (fru.) and sucrose (suc.). The total sugar contents of the two cucumber cultivars were generally similar under control conditions. In the other species the total sugar contents were about double those in the cucumbers. Fructose and glucose accounted for more than 50% of the sugar content in control plants of all species, reaching 86% in C. pepo, together with varying proportions of mannitol, inositol, sucrose, and raffinose. The proportions of the hexoses, fructose and glucose tended to decrease with stress in two cucumber cultivars compared with control plants. In the other Cucurbitaceae species, the proportion of hexoses showed no changes with water stress, apart from an apparent rise in Acur under MS. The raffinose percentages were lower in extracts prepared after the recovery time, showed no differences between previously stressed and unstressed plants whereas inositol formed similar proportion of total sugars at the end of stress treatments. © 2007, American-Eurasian Network for Scientific Information.